DEVELOPMENT OF TRANSPORT COMMUNICATION SYSTEM IN THE REPUBLIC OF UZBEKISTAN (American Journal of Technology and Applied Sciences, 2023)
This article talks about the development of the transport communication system in the Republic of Uzbekistan. Based on archival data, the author analyzed the problem based on the existing scientific literature and studied the existing specific aspects of the development of the transport communication system in the Republic of Uzbekistan.